Measurements of translation initiation from all 64 codons in E. coli. Issue 7 (21st February 2017) - Hecht, Ariel; Glasgow, Jeff; Jaschke, Paul R.; Bawazer, Lukmaan A.; Munson, Matthew S.; Cochran, Jennifer R.; Endy, Drew; Salit, Marc
Abstract: Our understanding of translation underpins our capacity to engineer living systems. The canonical start codon (AUG) and a few near-cognates (GUG, UUG) are considered as the 'start codons' for translation initiation in Escherichia coli . Translation is typically not thought to initiate from the 61 remaining codons. Here, we quantified translation initiation of green fluorescent protein and nanoluciferase in E. coli from all 64 triplet codons and across a range of DNA copy number. We detected initiation of protein synthesis above measurement background for 47 codons. Translation from non-canonical start codons ranged from 0.007 to 3% relative to translation from AUG. Translation from 17 non-AUG codons exceeded the highest reported rates of non-cognate codon recognition. Translation initiation from non-canonical start codons may contribute to the synthesis of peptides in both natural and synthetic biological systems.